Is the Markowitz Model Still Effective in Forming an Optimal Stock Portfolio? Empirical Evidence from the IDX ESG Leaders Index - Erik Syawal Alghifari; Ardi Gunardi; Nugraha Nugraha; Ika Waspada; Maya Sari (Universitas Pasundan, 2023)
The current portfolio calculation was basically developed by Markowitz (1952) who gave rise to the Modern Portfolio Theory. However, along with the development of science, other models emerged in portfolio calculation. This study tried to provide a flashback to whether the Markowitz portfolio model is still effective in forming an optimal portfolio compared to other portfolio calculation models. This study used descriptive research with a quantitative approach. This study used secondary data in the form of daily stock prices of companies, including the IDX ESG Leaders Index on the Indonesia Stock Exchange for the period of December 2020 to March 2022. The results showed that 11 stocks out of 25 stock samples were included in the optimal portfolio in both the Markowitz model and the Single Index Model but with different stock compositions. In terms of portfolio performance, the Markowitz model is still superior to the Single Index Model. This can be seen from the calculation results of the three indexes used, including the Sharpe Index, Treynor Index, and Jensen Index. This study provided an important contribution that the Markowitz model portfolio formation can be used and has proven to perform well in the formation of a stock portfolio.